2021
DOI: 10.7717/peerj.11278
|View full text |Cite
|
Sign up to set email alerts
|

The paeonol target gene autophagy-related 5 has a potential therapeutic value in psoriasis treatment

Abstract: Background Paeonol is a potent therapy for psoriasis. This study aimed to screen out paeonol-targeted genes in psoriasis and validate the potential of using paeonol for the management of psoriasis. Methods Microarray datasets were obtained from the Gene Expression Omnibus. The differentially expressed genes (DEGs) in the lesional skin samples and the overlapping genes between DEGs and paeonol- and psoriasis-related genes were defined as pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Two main active compounds, paeonol and astilbin, have been found effective in managing psoriasis. Previous studies have shown that paeonol can regulate the expression of gene autophagy-related 5 to manage psoriasis in vitro [ 31 ], and inhibit the maturation and activation of dendritic cells, leading to the amelioration of imiquimod-induced psoriasis-like skin lesions in vivo [ 32 ]. Similarly, topical application of astilbin has been found to inhibit the dendritic cell-Th17 inflammation axis and improve imiquimod-induced psoriasis-like skin lesions in SKH-1 mice [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two main active compounds, paeonol and astilbin, have been found effective in managing psoriasis. Previous studies have shown that paeonol can regulate the expression of gene autophagy-related 5 to manage psoriasis in vitro [ 31 ], and inhibit the maturation and activation of dendritic cells, leading to the amelioration of imiquimod-induced psoriasis-like skin lesions in vivo [ 32 ]. Similarly, topical application of astilbin has been found to inhibit the dendritic cell-Th17 inflammation axis and improve imiquimod-induced psoriasis-like skin lesions in SKH-1 mice [ 33 ].…”
Section: Methodsmentioning
confidence: 99%